Unstructured cellular automata in ecohydraulics modelling - Lin, Yuqing (CRC Press/Balkema, 2014)
The field of ecohydraulics integrates hydrodynamic and eco-dynamic processes. While hydrodynamic processes are usually well described by partial differential equations (PDE's) based on physical conservation principles, ecosystem dynamics often involve specific interactions at the local scale. Because of this, Cellular Automata (CA) are a viable paradigm in ecosystem modelling. All cells in a CA system update their states synchronously at discrete steps according to simple local rules. The classical CA configuration consists of uniformly distributed cells on a structured grid. But in the field of hydrodynamics, the use of unstructured grids has become more and more popular due to its flexibility to handle arbitrary geometries.